ARTISTICITY IN THE STORY GENRE (Web of Teachers: Inderscience Research, 2024)
If we take into account that there are always psychological problems in the short story genre, the essence of the problem becomes clear. It is clear that only one-sided study of the problem does not fit the dimensions of our research.